The role of trigger factors in the development of systemic sclerosis (clinical case) - I. V. Menshikova; Y. V. Pak; M. F. Petrukhnova; O. I. Mochalova (Современная ревматология, 2023)
A clinical case of the development of rapidly progressive systemic sclerosis after repeated coronavirus infection is described. The contribution of occupational hazards, the oncological process and radiation therapy to the pathogenesis of this disease is discussed. Hydropericardium was a feature of the clinical picture, as well as rare immunological markers of the late onset of systemic sclerosis.